Three-dimensional reconstruction of bifilm defects. (15th January 2021) - Song, Heqian; Zhang, Lunyong; Cao, Fuyang; Shen, Hongxian; Ning, Zhiliang; Huang, Yongjiang; Zhao, Xinyi; Gu, Xu; Qiu, Ziao; Sun, Jianfei
Abstract: Bifilm defects have been proposed to be critical for the generation of various metallurgical defects in castings and have been reported to exist in various composition-based alloys. However, the geometry structure of bifilm defects has not yet been well understood. This present work reconstructed the bifilm defects in a nickel-aluminium bronze alloy casting in three-dimensional (3D) space through the use of computer tomography technology. It was shown that the shape of the bifilm defects is very complex and different from a spherical defect in 3D space. The bifilm defects were experimentally extracted successfully by an electrolysis method and were imaged, which confirmed the folded double-layer structure of the bifilm defects. These results will shed new light on the understanding of bifilm defects and improve the defect control engineering of castings. Graphical abstract: Image, graphical abstract